A Comparative Study of Result of Treatment of Cancer Cervix Patients Treated by Two Separate Schedules of Radiotherapy (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Background: Cervical cancer is the most common cancer of Bangladeshi women diagnosed mostly (>80%) at stage II and stage III. Rdaiotherapy (both teletherapy and brachytherapy) is the most important modality of treatment at these stages.Objective: To compare the local control, diseases free survival and overall survival between the (cancer cervix) patients treated randomly by two schedules of radiotherapy. Method: From June 1996 to June 2005, patients with histologically confirmed carcinoma cervix (Ca.cervix) were treated by external beam therapy (EBRT) as well as intra cavitery brachytherapy (ICRT) along with concurrent/sequential chemotherapy with cisplatin and 5- Fluorouracil. EBRT was given by cobalt60 teletherapy machine and ICRT by caesium137 low dose rate machine. The patients were divided into two groups according to treatment schedules. Group I: the patients in this group received EBRT in whole pelvis in two steps, first with open field upto 10-20 Gy then by applying midline shield with lead block 30-40Gy in 25-28 total fractions, five days a week; they also received 50-70 Gy to point A by ICRT in 2-4 weekly fractions. Group II: patients in this group received with open field a dose of 45-50Gy in 25-28 fractions, 5 days a week by EBRT and 25-30 Gy at point A by ICRT in 1-2 weekly fractions.Result: In Group I, 96 out of 101 and in Group II, 104 out of 118 patients were eligible for evaluation. In both groups patients were distributed according to stages and age more or less equally; their age range were 30-70 years and mean age was 47.2 years in Group I and age range were 25-80 years and mean age was 46 years in Group II. Squamous cell carcinoma were found (90%) and performance status was WHO grade 0-1 (>75%) in both groups. Local control of disease at 5 years was 65% in group I and 51% in group II. Overall survival at 2 years, 5 years, 7 years and 9 years in group I, was 71%, 64%, 55%, 46% and in group II, 54%,50%, 43%,32% respectively. Distant metastasis occurred in 22% in-group I and 28% in-group II. Lymph node, lung, liver, peritoneum were common site of metastasis. Proctitis, cystitis, vaginal stenosis in group I was 80%, 33% 16% and in Group II 29%, 13% and 5% respectively. Conclusion: External beam therapy and brachytherapy was effective treatment in carcinoma. Cervix in both operable and inoperable stages. In small volume of tumor, both schedules of radiotherapy were more or less equivalent but in bulky diseases Group I schedule that was higher dose by brachytherapy at point A showed better result; though the complication was more DOI: http://dx.doi.org/10.3329/bjog.v25i2.13739 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 50-58